Molecular determination of genetic variability, pre-flowering sex, and chemotype in medicinal Cannabis sativa varieties cultivated in Northwestern Buenos Aires - Lopez Miro, Daniela; Prece, Natalia María; Introna, Jimena; Llanes, Martin Raul; Rivoltella, Luciano Alberto; Gómez, M.; Farroni, Abel Eduardo; Delucchi, Carla; Affinito, María Agostina; Roldan, Maria Lorena (2025)
Poster y resumen